Blind estimation of spreading sequence of CDMA signals based on Fast-ICA and performance analysis - LU Feng-bo; HUANG Zhi-tao; JIANG Wen-li (Tongxin xuebao)
The DS-CDMA signals can be divided into two types,the short-code（SC） and the long-code（LC） DS-CDMA signal.The existing methods are only used to estimate spreading sequences of SC-DS-CDMA signals,which cannot work for the LC-DS-CDMA signals.A new blind estimation algorithm for DS-CDMA signals based on fast independent com-ponent analysis was proposed by analyzing the mathematical model of the LC-DS-CDMA signal and the estimation per-formance of the proposed algorithm in theory was deduced.Moreover,the proposed method not only applies to the LC-DS-CDMA but also SC-DS-CDMA signals.The theoretical analysis and simulation results verify the effectiveness of the proposed algorithm.